Using organisational cultural theory to understand workplace interventions to reduce sedentary time. Issue 1 (2nd January 2017) - Such, Elizabeth; Mutrie, Nanette
Abstract : Sedentary behaviour has been shown to have a negative impact on health. As such, prolonged sitting in the workplace is being increasingly seen as a public health problem. Multi-component interventions to reduce sedentary time at work are being used as a way of addressing the different environmental, personal and organisational influences on sedentary behaviour. The role of the organisational context on behaviour has rarely been explored in depth or theorised in the sedentary workplace behaviour literature yet a rich body of theory and evidence exists outside the field. The current article applies an organisational cultural framework for exploring how organisational factors and dynamics impact on sedentary behaviour in the workplace. Empirical data are taken from a qualitative study of office workers' responses to a 'sit less' initiative. Thirteen in-depth interviews and documentary analysis were conducted to help elucidate the ways in which organisational assumptions, strategy, structures, activities, operations, actions and norms combine to constrain reduced sitting time at work. The article offers a theoretical approach to understanding how organisational culture can influence interventions aimed at encouraging people to sit less in the workplace. It also offers an opportunity to consider how intervention design can better account for the 'whole systems' of an organisation and how 'sit less' initiatives can be positioned within them.